Pengendalian Kualitas Data Atribut Multivariat dengan Mahalanobis Distance dan T2 Hotelling (Studi Kasus PT Metec Semarang) - Anggoro, Alfahari; Mustafid, Mustafid; Rahmawati, Rita (Department of Statistics, Faculty of Science and Mathematics, Universitas Diponegoro, 2016)
Vending machine is a machine used to sell the product automatically without any operator. Data vending machine products are classifiable in the attribute data for the category of disabled and not disabled. To maintain consistency of product quality and in accordance with market needs, it is necessary to do quality control on the activity undertaken. In the production process, to monitor the quality of service can be used multivariate control charts. Diagram control is often used is the Mahalanobis Distance and T2 Hotelling. The study was conducted on the data of defects in the production of vending machines in September 2013 to April 2015. Results showed that in the control diagram Mahalanobis Distance acquired upper limit value is 15.615 the control diagram is known there are two observations that are outside the control limits. While the T2 Hotelling control chart obtained upper limit value is 36.12 and all observations are within control limits. The production process has been good vending machine, known from the process capability of Cp value of 1.1503.Keywords: Vending Machine, Mahalanobis Distance, T2 Hotelling